2016
DOI: 10.1142/s1230161216500207
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Simulation of Two Interacting Schrödinger Particles

Abstract: In this paper, we examine whether a quantum computer can efficiently simulate time evolution of two Schrödinger particles. We consider particles interacting with each other and with an external potential. In order to solve the Schrödinger equation in the quantum register, we use an algorithm based on the quantum Fourier transform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In our previous work [20] we examined only the elastic collision of the Schrödinger particles. Here, for the first time, we simulate an inelastic scattering and return of the shield to the ground state by the photon emission.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work [20] we examined only the elastic collision of the Schrödinger particles. Here, for the first time, we simulate an inelastic scattering and return of the shield to the ground state by the photon emission.…”
Section: Introductionmentioning
confidence: 99%
“…In our earlier works we have shown that also rectangular potentials (like thresholds and wells) can be simulated using this method. This provides the ability to examine other interesting processes, such as the tunnel effect [19] and scattering of two Schrödinger particles to each other [20]. The present study also makes use of this kind of potential to simulate interaction between Schrödinger particle and shield.…”
mentioning
confidence: 99%